PERANCANGAN SISTEM PAKAR UNTUK IDENTIFIKASI KERUSAKAN HARDWARE DAN SOFTWARE PADA SMARTPHONE DENGAN MENGGUNAKAN METODE FORWARD CHAINING - Asrianto, Rudy; Araafy (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
Smartphone is a mobile phone that has the ability to use and function like a computer. The use of smartphones that are too frequent is one of the factors that trigger the damage caused, such as falling, being exposed to water or using the wrong way in everyday life. To help or protect smartphone users from deceit and cheating service workers that often occur today, an expert system is designed to detect hardware and software damage that occurs on smartphones in the form of applications. With this expert system, even ordinary people can find out the damage that occurs to smartphones which can only be obtained with the help of experts in their fields. This expert system is made using PHP and MySQL database so as to produce a web-based expert system to identify smartphone damage using the forward chaining method.